Morphological and physiological traits reveal differential salinity tolerance of two contrasting Glandularia cultivars - Di Filippo, Marina Laura; Baldassini, Pablo; Vila, Hernan Felix (Springer, 2020)
In view of the current, continuous decrease of water availability, the need to explore new mitigation alternatives has given focus to salt-tolerant genotypes. The aim of this work was to study salt tolerance of two ornamental cultivars of Glandularia (Glandularia x hybrida) of contrasting vigor, Dulce Coral and Extrema Violeta, breeded at the Floriculture Institute of INTA. A greenhouse experiment was carried out with potted plants. Plants were subjected to four salt treatments 1.2, 2.4, 3.5, 4.4 dS m−1 (EC), and a control (0.03 dS m−1). Shoot dry weight of Dulce Coral was not affected by salinity. In contrast, the dry weight of Extrema Violeta decreased sharply as salinity increased. The root:shoot ratio was always higher for Extrema Violeta than Dulce Coral. The leaves of Dulce Coral accumulated less Na+ and Cl− than Extrema Violeta. Moreover, Extrema Violeta exhibited severe foliar salt damage, but Dulce Coral showed only a few, without compromising its commercial value. Besides, Dulce Coral had a higher assimilation rate than Extrema Violeta at all treatments. All these features could suggest Na+ and Cl− exclusion as salt-tolerant mechanism for Dulce Coral. Other mechanisms adopted by Dulce Coral to cope with salinity was the maintenance of a higher K+/Na+ and Ca2+/Na+ ratio in its leaves, a lower root:shoot ratio and the maintenance of photosynthesis. Therefore, Dulce Coral could be proposed as a parent for breeding programs with the objective of improving salt tolerance in Glandularia. In this exploratory study, we distinguish some of the most important physiological (K+/Na+ and Ca2+/Na+) and morphological (root:shoot ratio) traits related to salinity tolerance in Glandularia.